Evolution of the HIV-1 Rev Response Element during Natural Infection Reveals Nucleotide Changes That Correlate with Altered Structure and Increased Activity over Time - Sherpa, Chringma (J Virol, 2019)
The HIV-1 Rev response element (RRE) is a cis-acting RNA element characterized by multiple stem-loops. Binding and multimerization of the HIV Rev protein on the RRE promote the nucleocytoplasmic export of incompletely spliced mRNAs, an essential step in HIV replication. Most of our understanding of the Rev-RRE regulatory axis comes from studies of lab-adapted HIV clones. However, in human infection, HIV evolves rapidly, and mechanistic studies of naturally occurring Rev and RRE sequences are essential to understanding this system. We previously described the functional activity of two RREs found in circulating viruses in a patient followed during the course of HIV infection. The early RRE was less functionally active than the late RRE, despite differing in sequence by only 4 nucleotides. In this study, we describe the sequence, function, and structural evolution of circulating RREs in this patient using plasma samples collected over 6 years of untreated infection. RRE sequence diversity varied over the course of infection, with evidence of selection pressure that led to sequence convergence as disease progressed being found. An increase in RRE functional activity was observed over time, and a key mutation was identified that correlates with a major conformational change in the RRE and increased functional activity. Additional mutations were found that may have contributed to increased activity as a result of greater Shannon entropy in RRE stem-loop II, which is key to primary Rev binding. IMPORTANCE HIV-1 replication requires interaction of the viral Rev protein with a cis-acting regulatory RNA, the Rev response element (RRE), whose sequence changes over time during infection within a single host. In this study, we show that the RRE is subject to selection pressure and that RREs from later time points in infection tend to have higher functional activity. Differences in RRE functional activity are attributable to specific changes in RNA structure. Our results suggest that RRE evolution during infection may be important for HIV pathogenesis and that efforts to develop therapies acting on this viral pathway should take this into account.